The Child’s Right In Custody and Foster Care In Saudi Arabia - Bayan Alsafwani (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2024)
The Personal Status Law of Saudi Arabia 2022 regulates all matters related to family issues including child custody. The best interest of a child should be taken into consideration while taking decisions, especially for girls who need a mother’s care and guidance. This legal research found limitations of women’s right to be custodians due to marrying another man. This provision is opposed to Shariah principles particularly to Suran An-Nisa Verse 23, and to international conventions. Therefore, the government of Saudi Arabia must study this issue and take immediate action to resolve the conflict of laws.